Pengetahuan sebagai Faktor Dominan bagi Perilaku Mencuci Tangan pada Anak - Mukaromah, Luluk Ul; Zainurridha, Yuly Abdi (FORIKES, 2025)
Handwashing behavior is the most basic disease prevention and control effort that can be taught to children. The purpose of this study was to identify factors influencing handwashing behavior in children. This study was a literature review involving a database, Google Scholar. Articles were searched using the keywords